Feasibility Study of a Fish By-Product Recovery Plant with a Processing Capacity of 1,000 kg/Day - Martins, Maria Inez Espagnoli Geraldo [UNESP]; da Costa, Jesaias Ismael [UNESP]; Gonçalves, Giovani Sampaio; Vidotti, Rose Meire (Taylor & Francis, 2016)
This study evaluates the feasibility of producing hamburger, silage, and leather using fish by-products in a medium-sized recovery plant with total capacity of processing up to 1,000 kg/day of whole fish. The average volume of fish by-products generated daily was 673 kg. The investment necessary to introduce these three technologies was US$47,193.13 in 1 year. The average cost to produce 1 kg of hamburger, silage, and leather was 1.24, 0.17, and US$1.77, respectively. The return of the investment was 56.16%, and the net present value US$570,582.16. The investment pay back was realized in 3.88 years, with a benefit/cost relationship of 1.31. For all the studied scenarios, sale price variations most influenced the economical parameters analyzed.
Keywords: Economic viability; hamburger; leather; silage; tilapia; value-added products